Firm Resources, Strategies, and Survival and Growth during COVID-19 : Evidence from Two-Wave Global Surveys - Fang, Sheng; Goh, Chorching; Li, Shaomin; Xu, L. Colin (World Bank, Washington, DC, 2022)
This study examines how firms have made strategic choices and performed during the COVID-19 pandemic. Drawing on the organizational resources and strategic change literature, it uses World Bank Enterprise Surveys and the COVID-19 Follow-up Enterprise Surveys to examine how different endowments in organizational resources affected firm performance as measured by their survival status and sales growth, and how these resources interact with and affect strategic responses in the supply of inputs, response to changing demand, liquidity management, and innovation. The results indicate that larger firms, firms with foreign or state ownership, and subsidiary companies performed better during the pandemic by more effectively stabilizing supply, managing liquidity, and fostering new product development. Chief executive officers with longer tenure improved survival rates. Firms in richer countries have coped with the pandemic better and stringent government COVID-19 control policies have tended to hurt firms' performance.